(3TQM GdMOhO GdfMhjIs - (3Ydj Hf CMeO Hf eMeO Hf jhSa GdQLQGLj GdLRhdj GdQSehcjs; (3CMeO Hf eMeO Hf eMeO GdHLGFj GdCnqHPlj, TgGH GdOjf,J (B860 (3g` s
(3ChdgG (B:s
(3bGd gPg MOhO, LeY MO hgh JaSjQ CedGg(B: (3ef CedjJ GdcJGH Cedjg s
(3BNQgG (B:s
(3MO GdUZQi eG hbYJ NHQkG deHJOC cLedI bGe CHhg aj GdeKGd GdePchQ, hef CeKdJgG RjO bGe, Ch bGe RjO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3ajg VHWs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B229 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B150s
Keywords: (3GdfMhs